The national and the popular in Israeli cinema - Avisar, Ilan (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Abstract. Avisar Ilan, The national and the popular in Israeli cinema. “Images” vol. XXV, no. 34. Poznań 2019. Adam Mickiewicz University Press. Pp. 29–44. ISSN 1731-450X. DOI 10.14746/i.2019.34.02. The article examines Israeli cinema as a critical participant in the local drama of national ideology and national identity. Israeli filmmakers have engaged in enunciating the national culture, in the context of the medium’s history, political ideologies, and the tension between high art and popular culture. The historical review of Israeli films shows dramatic changes over the years from nationalistic propaganda to radical critique and post-Zionism. Israeli cinema appears now to seek a constructive and fruitful dialogue with the viewers. In the recent wave of popular films, the national ideology is more conscious of its past mistakes and inherent deficiencies; its presentation of national identity is less narrow and more open to alternative types, thereby suggesting new vistas of national culture